ANALYSIS OF THE APPLICATION OF GAME BASE LEARNING IN VOCATIONAL EDUCATION OF LATHE MACHINING - Abdissalam, Muhammad Wifaqurrokhman; Ari Dwi Nur Indriawan Musyono; Kriswanto; Yudiono, Heri (Universitas Negeri Semarang, 2025)
This article examines the implementation of the Game-Based Learning (GBL) model in lathe machining education at vocational high schools (SMK). Lathe machining is a manufacturing process that produces cylindrical machine components using a lathe, in which the workpiece rotates and is subjected to a single-point cutting tool aligned with the workpiece axis. To improve the quality of lathe machining education, an effective instructional model such as Game-Based Learning is needed. This research applies a Systematic Literature Review (SLR) approach to identify and analyze six relevant studies published between 2020 and 2025 based on inclusion criteria. The findings show that GBL has a positive impact on increasing students’ learning motivation, engagement, and learning outcomes in lathe machining practice. The study concludes that GBL is an effective solution for practice-based learning in vocational education and recommends its wider adoption in technical vocational training.